STRATEGI INOVATIF GURU PENDIDIKAN AGAMA ISLAM DI ERA SOCIETY 5.0 - Anida Anida (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
The era of society is a refinement of the previous industrial era 4.0. The era of society shows a minimal human role which all leads to the use of machines or ICT in various fields. This era has an impact on all lines of life including the education sector. For this reason, Islamic religious education needs to improve and innovate learning strategies to be better and in accordance with the times. This research is library research by analyzing related studies to produce a conclusion regarding the innovative strategy of Islamic education in the era of society 5.0. through this study shows that one of the things that needs to be done in Islamic education is to change the paradigm of thinking about the concept of Islamic learning and opening oneself to new things as a support for accelerating the understanding of religious objects in students. This includes getting used to the learning process using the e-learning system with an interesting approach and adapting to the environment.